Water, Wood and Wonder: Contemplative Thought in Thomas Merton and Sergio Bongiovanni - Guadalupe Zorrilla, María (The Merton annual, 2025)
This article examines points of convergence between Thomas Merton's contemplative thought and Sergio Bongiovanni's Lo que cuentan los ríos (2013), focusing on how both authors frame the human-nature relationship. In both Merton's writings and Bongiovanni's portrayals of the landscapes and communities of Mendoza, Argentina, nature is not treated as background or motif; it functions as an active context that informs perception, conduct and responsibility. The paper situates both authors within broader critiques of anthropocentrism and linguistic alienation from the natural world, ultimately arguing that Bongiovanni and Merton converge in portraying nature as a contemplative space where the human self is reawakened to its interdependence, fostering ecological responsibility and deeper self-understanding.